Relationships between mortality, morbidity, and physical function in adults who survived a period of prolonged mechanical ventilation - Hill, Kylie; Dennis, D.; Patman, S. (W.B. Saunders Co., 2013)
Purpose: This study aimed to report mortality, morbidity, and the relationship between these outcomes with physical function in patients who survived prolonged mechanical ventilation during an intensive care unit (ICU) admission. Methods and Materials: Records were reviewed for Western Australian residents admitted to an ICU in 2007 or 2008 who were ventilated for 7 days or longer and survived their acute care stay. Records were linked with data maintained by the Department of Health. Results: A total of 181 patients (aged 52 ± 19 years) were included in this study. In the 12 months after discharge, 159 (88%) survived and 148 (82%) had been hospitalized. Compared with those who were ambulating independently when discharged from acute care, those who were not had more admissions (incident rate ratio, 1.81; 95% confidence interval, 1.28-2.57) and a greater cumulative length of hospital stay (10 [37] vs 57 [115] days, P < .001) over the first 12 months after discharge. Time between admission to ICU and when the patient first stood correlated with the number of admissions (Rs = 0.320, P < .001) and cumulative length of stay (Rs = 0.426, P < .001) in the 12 months after discharge. Conclusions: For survivors of prolonged mechanical ventilation, physical function during acute care was associated with hospitalization over the following 12 months.